Current perspectives on deep brain stimulation for severe neurological and psychiatric disorders - Kocabicak E (Dove Medical Press, 2015)
Ersoy Kocabicak,1–3 Yasin Temel,1,2 Anke Höllig,4 Björn Falkenburger,5 Sonny KH Tan2,4 1Department of Neurosurgery, Maastricht University Medical Centre, 2Department of Neuroscience, Maastricht University, Maastricht, the Netherlands; 3Department of Neurosurgery, Ondokuz Mayis University, Samsun, Turkey; 4Department of Neurosurgery, 5Department of Neurology, RWTH Aachen University, Aachen, Germany Abstract: Deep brain stimulation (DBS) has become a well-accepted therapy to treat movement disorders, including Parkinson’s disease, essential tremor, and dystonia. Long-term follow-up studies have demonstrated sustained improvement in motor symptoms and quality of life. DBS offers the opportunity to selectively modulate the targeted brain regions and related networks. Moreover, stimulation can be adjusted according to individual patients’ demands, and stimulation is reversible. This has led to the introduction of DBS as a treatment for further neurological and psychiatric disorders and many clinical studies investigating the efficacy of stimulating various brain regions in order to alleviate severe neurological or psychiatric disorders including epilepsy, major depression, and obsessive–compulsive disorder. In this review, we provide an overview of accepted and experimental indications for DBS therapy and the corresponding anatomical targets. Keywords: deep brain stimulation, movement disorders, neurological disorders, psychiatric disorders, Parkinson’s disease